Problems Faced in Using Safety in The Working Environment and How to Overcome Them in Sidewalk Development Projects and Footway Facilities in Kemang South Jakarta - Sempurna Bangun (Kusuma Negara Business School, 2020)
The construction service community implements and emphasizes Work Safety for the good of workers and it is actually not as difficult as imagined, Things that are considered difficult can become not difficult if your work area complies with good and precise safety rules, besides leading with full discipline and by cultivating strong trust among the work team. Efforts to reduce the number of work accidents as small as possible are used in the prevention and handling of work accidents, namely the Behavior Based Safety (BBS) safety program and the Patrol program implemented by the General of Affair and Environmental Health System Operational (GA & EHS). so that it was successful, the aim of this study was to analyze the effectiveness of the BBS program in changing the attitudes of employees related to the use of personal protective equipment in the workplace. The results show that most workers do not understand personal protective equipment and do not care about the punishment agreed upon by the company. Thus, the solution of this study is expected to solve problems and strengthen positive behavior and work safety in the workplace. Occupational Health and Safety Management System (SMK3) is a security protection system for work stress and safety, safety and security loss and safety humans and the surrounding environment which in turn can improve effective and efficient performance. Education on the implementation of SMK3 in Indonesia is regulated in the Minister of Manpower No.01 / MEN / 1980 (K3 building construction), Permenaker No.5 / 1996 (SMK3), Inst. Menaker No.01 / 1992 (K3 Organizational Unit Inspection), Decree of the Director General of PPK No. 20DJPPK / VI / 2004 (K3 Expert).